U.S. Climate Technology Plan. - Barlas, S.
This paper presents the Climate Change Technology Strategic Program Plan, released by the U.S. Department of Energy (DOE). It evaluates all relevant greenhouse gas mitigation technologies and identifies the various sources of government support for development of the technologies. It is also the first time that federal spending on greenhouse mitigation technology has been detailed and combined into a complete plan
Keywords: Climate Change Technology Strategic Program Plan; DOE; USA Department of Energy; Government support; Greenhouse gas mitigation technologies